Manufacturing execution systems : optimal design, planning, and deployment. - Meyer, Heiko, ....-; Fuchs, Franz, ....-; Thiel, Klaus, ....- (New York : McGraw-Hill, 2009)
Streamline the production process from top-tier management to the plant floor using cutting-edge MES tools and techniques. Manufacturing Execution Systems shows, step-by-step, how to select hardware and software, develop implementation plans, and maintain an integrated MES solution across your entire enterprise. Learn how to maximize process capability, generate manufacturing intelligence, handle order fulfillment and QA, and ensure optimal ROI. This practical guide includes real-world case studies, predictions for the future of production-oriented IT systems, and detailed technical appendices. Understand and apply MES, CPM, and integration concepts Analyze and assess the advantages of different MES solutions Dynamically map and model your facility, from supply chain to output Manage plant data, business information, and standards compliance Increase production efficiency using TQM and Lean techniques Carry out production flow-oriented design and sequence planning Govern order fulfillment, quality control, and plant maintenance Incorporate human resources, ERP, and product lifecycleinformation